Regasification of liquefied natural gas in satellite terminals: Techno-economic potential of cold recovery for boosting the efficiency of refrigerated facilities - Atienza Márquez, Antonio; Bruno, Joan Carles; Coronas, Alberto (Elsevier, 2021)
The regasification of liquefied natural gas releases low-temperature thermal energy, which is usually wasted. Most initiatives to recover this cold mainly focus on large-scale harbour terminals rather than on small-scale applications in satellite facilities. This paper proposes a new system configuration that can be used to exploit liquefied natural gas cold as a by-product of regasification in satellite plants supplying sub-zero refrigeration in agro-food industries. Cold is applied indirectly to lower the condensation temperature of the vapour-compression chillers which handle the thermal load of cold rooms. The system seeks to boost efficiency, an effect that would be more marked in warm climates. Performance is best when the peak refrigeration load matches the maximum cold thermal energy available from the regasification site. When this is the case, the annual electricity saving is 9–22% more than when a conventional refrigeration system is used with wet cooling towers and with no liquefied natural gas cold recovery. The economic potential of the system is assessed with a Monte Carlo analysis. The cost of producing refrigeration throughout the system’s lifetime can be reduced by 5–15% with respect to the conventional reference system in warm/temperate locations and for large/medium plant sizes. However, the system is no so competitive in economic terms for cold locations and small-size plants.
Keywords: Gas natural licuado; Liquefied natural gas regasification; Satellite LNG terminals; Cold recovery; Energy efficiency improvement; Sustainable refrigeration; Techno-economic potential